“And in Length of Days Understanding” (Job 12:12)
XXVIII, 1970 p. 1 illus.
Keywords: This two-volume book presents cutting-edge archaeological research, primarily as practiced in the Eastern Mediterranean region. These volumes’ key foci are inspired by the work of Thomas E. Levy. Volume 1 provides an in-depth look at new archaeological research in the southern Levant (primarily in modern Israel and Jordan) inspired by Levy’s commitment to understanding social, political, and economic processes in a long-term or “deep time” perspective. Volume 2 focuses on new research in several key areas of 21st century anthropological archaeology and archaeological science. Volume 1 is organized around two major themes: 1) the later prehistory of the southern Levant, or the Neolithic, Chalcolithic, and Bronze Age, and 2) new research in biblical archaeology, or the historical archaeology of the Iron Age. Each section contains a combination of new perspectives on key debates and studies introducing new research questions and directions. Volume 2 is organized around fivemajor themes: 1) the archaeology of the Faynan copper ore district of southern Jordan, a key region for archaeometallurgical research in West Asia where Levy conducted field research for over a decade, 2) new research in archaeometallurgy beyond the Faynan region, 3) marine and maritime archaeology, focusing on issues of trade and environmental change, 4) cyber-archaeology, an important 21st century field Levy conceived as “the marriage of archaeology, engineering, computer science, and the natural sciences,” and 5) key issues in anthropological archaeological theory. In addition to presenting the reader with an up-to-date view of research in each of these areas, the volume also has chapters exploring the connections between these themes, e.g. the maritime trade of metals and cyber-/digital archaeological approaches to metallurgy. The work contains contributions from both up-and-coming early career researchers and key established figures in their fields. This book is an essential reference for archaeologists and scholars in related disciplines working in the southern Levant and the Eastern Mediterranean.